Crystal structure and EPR spectrum of dimeric di-μ-azide-bis[cyanide(N,N-diethylethylenediamine)]-copper(II), [Cu(N₃)(NCO)(diEten)]₂ - Piro, Oscar Enrique (1997)
The title compound, [Cu(N₃)(NCO)(C₆H₁₆N₂)]₂, crystallizes in the space groupP2₁/n, witha=8.336(1),b=17.405(3),c=8.376(1) Å, β=109.73(2)o andZ=4. The molecules are arranged as centrosymmetric dimers in which two azide ligands bridge neighboring copper ions in an asymmetric head-on fashion. The Cu(II) ion is coordinated to five nitrogen atoms which form a distorted tetragonal pyramid. At the pyramid base are the two N atoms of a diEten molecule [Cu−N=2.00(1), 2.130(9) Å], an azide end atom [Cu−N=1.99(1) Å] and a NCO group [Cu−N=1.93(1) Å]. At the pyramid apex is the other, inversion related, azide N atom in the dimer [Cu−N=2.38(1) Å]. This Cu−N contact links the monomers within a dimer. Neighboring dimers are coupled by weak N−H…O contacts. Single crystal EPR data at X-band show that the pair of resonances expected for neighboring, magnetically nonequivalents dimers, collapse into a single line, a signature of inter-dimers superexchange coupling. The observed crystal gyromagnetic tensor is used to disclose the electronic and magnetic structure around Cu(II) ions.